Changes in Emotional-Behavioral Functioning Among Pre-school Children Following the Initial Stage Danish COVID-19 Lockdown and Home Confinement - Specht, Ina Olmer; Rohde, Jeanett Friis; Nielsen, Ann-Kristine; Larsen, Sofus Christian; Heitmann, Berit Lilienthal (Frontiers in Psychology, 2021)
Unintended negative outcomes on child behavior due to lockdown and home confinement following the corona virus disease (COVID-19) pandemic needs highlighting to effectively address these issues in the current and future health crises. In this sub-study of the ODIN-study, the objectives were to determine whether the Danish lockdown and home confinement following the COVID-19 pandemic affected changes in emotional-behavioral functioning of pre-school-aged children using the validated Strength and Difficulties Questionnaire (SDQ) answered by parents shortly before lockdown and 3 weeks into lockdown, and moreover, to examine whether baseline family and social characteristics could predict change in child emotional-behavioral functioning during lockdown. Parents of 40 (82%) children with a mean(SD) age of 5.0(0.7) completed the baseline questionnaire and the lockdown follow-up questionnaire. The SDQ-Total difficulties score (SDQ-TD) and Prosocial Behavioral score (PSB) changed significantly from pre- to lockdown [SDQ-TD mean(SD): 6.0(3.8) and 7.9(5.2); P = 0.02, respectively and PSB mean(SD): 8.5(1.4) and 7.9(1.5); P = 0.03, respectively]. Attending leisure time activities before lockdown was a predicting factor of changes to the worse in the children’s SDQ-TD scores, with a mean difference in SDQ-TD between those with and without activities of 3.16 (95%CI 0.27–6.12); P = 0.03. In conclusion, the study showed a modest decrease in child-emotional behavioral functioning during the COVID-19 lockdown, potentially due to parental stress. Although these results might not be generalizable due to small sample size and selected population, the results point to a need of a greater awareness of child mental wellbeing during a lockdown situation.